Association between the time spent watching television and the sociodemographic characteristics with the presence of overweight and obesity in Colombian adolescents (secondary analysis of the ENSIN 2010). - David Rincón-Pabón; Yeraldin Urazán-Hernández; Jhonatan González-Santamaría (PLoS ONE, 2019)
Objective To determine the association between the time spent watching television and the sociodemographic characteristics with the presence of overweight and obesity in Colombian adolescents. Materials and methods Secondary analysis of the information obtained in the National Survey of the Nutritional Situation 2010 of Colombia, in a probabilistic sample of 18177 adolescents with an age range between 13 and 17 years. The time spent watching television and / or videogames and sociodemographic factors was determined. Anthropometric markers and body composition were recorded. Associations were established through logistic regression models. Results The prevalence of overweight was 13.0% (95% CI 12.4-13.8) and obesity was 3.0% (95% CI 2.8-3.3). The prevalences of overweight and obesity were higher in adolescent women [16.6% (95% CI 15.8-17.5) and 3.4% (95% CI 3.1-3.7), respectively]. Overweight and obesity were associated with being female [OR 1.94 (95%CI 1.77-2.12) and OR 1.29 (95%CI 1.09-1.53), respectively], high socioeconomic level [OR 1.22 (95%CI 1.10-1.36) and OR 1.47 (95%CI 1.19-1.81), respectively], reside in urban area [OR 1.13 (95%CI 1.03-1.24) and OR 1.47 (95%CI 1.21-1.79), respectively]. Being indigenous was associated with being overweight [OR 1.25 (95%CI 1.10-1.42)], while being Afro-Colombian was associated with obesity [OR 1.33 (95%CI 1.05-1.69)]. Watching television and / or video games for two or more hours a day [OR1.17 (95%CI 1.06-1.30)] was associated with being overweight; whereas watching television every day of the week was associated with obesity [OR 1.66 (95%CI 1.13-2.43)]. Conclusions The population studied has a significant prevalence of overweight and obesity, being overweight is associated with being a woman, a high socioeconomic status, residing in an urban area, having an indigenous ethnicity, watching television for three days during the week and looking at more than two hours of television in a day; Obesity is associated with being a woman, a medium-high and high socioeconomic status, residing in an urban area, Afro-Colombian ethnicity, watching television at least once in the last week and watching television every day during the last week.